2021
DOI: 10.1155/2021/7992688
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture Synergistically Inhibits Proinflammatory Cytokine Production and Improves Cognitive Function in Rats with Cognitive Impairment due to Hepatic Encephalopathy through p38MAPK/STAT3 and TLR4/NF-κB Signaling Pathways

Abstract: Objective. To investigate the effect of electroacupuncture (EA) on cognitive dysfunction in rats with hepatic encephalopathy and its underlying mechanism. Methods. Fifty Wistar rats were randomly divided into a normal group (n = 10) and model group (n = 40). Rat models of hepatic encephalopathy were established by administration of carbon tetrachloride and thioacetamide for a total of 12 weeks. At the 9th week after modeling, rats with cognitive impairment in the model group were identified by conducting the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Acupuncture at GV20 and ST36 suppressed TLR4 expression in the hippocampal microglia of VD rats, accompanied by reduced activation of miR-93 and myeloid differentiation primary response 88 (MyD88)/NF-κB signaling, suggesting that acupuncture may attenuate inflammation-related cognitive impairment by inhibiting miR-93-mediated TLR4/MyD88/NF-κB signaling in VD rats [ 81 ]. Other studies using EA reported similar results, implying that TLR4/MyD88/NF-κB signaling may have mediated EA’s effect in rats with VD and hepatic encephalopathy [ 82 , 83 ].…”
Section: Methodsmentioning
confidence: 53%
“…Acupuncture at GV20 and ST36 suppressed TLR4 expression in the hippocampal microglia of VD rats, accompanied by reduced activation of miR-93 and myeloid differentiation primary response 88 (MyD88)/NF-κB signaling, suggesting that acupuncture may attenuate inflammation-related cognitive impairment by inhibiting miR-93-mediated TLR4/MyD88/NF-κB signaling in VD rats [ 81 ]. Other studies using EA reported similar results, implying that TLR4/MyD88/NF-κB signaling may have mediated EA’s effect in rats with VD and hepatic encephalopathy [ 82 , 83 ].…”
Section: Methodsmentioning
confidence: 53%
“…Evidence-Based Complementary and Alternative Medicine was the most productive journal in acupuncture and glial cells, and unsurprisingly, this journal was also the most active journal with the maximum number of articles in other acupuncture-related academic fields such as acupuncture and metabolomics, acupuncture and microbiology, and acupuncture and molecular biology. [32,33] In contrast, despite the fact that Korea has no publishers, it is one of the most important countries for acupuncture and glial cell research. Although, China has 3 of the top 10 ranked publishers, it lacks academic journals with a Journal Citation Report partition of Q1.…”
Section: Discussionmentioning
confidence: 99%
“…All puncture points were connected to Han's Electroacupuncture instrument. After reviewing the literature [ 22 , 23 ], EA was performed using a stimulation current of 1 mA, frequency of 15 Hz, duration of 30 min, and once a day [ 14 ].…”
Section: Methodsmentioning
confidence: 99%